Modernising the Education System to Confront Realities of 21st Century Digital Space in Sierra Leone: a Practical Discourse - Jackson, Emerson Abraham (Educational Challenges, 2022)
The article has provided an opportunity for critical discourses geared towards the modernisation of education in Sierra Leone to confront the realities of digital transformation in the 21st century. The purpose of the study is carved towards the achievement of addressing three objectives, which include the assessment of technology provision and gaps in the country, and proffering recommendations geared towards edging the country’s hope of making realistic growth prospects that is comparable to its counterparts in the Sub-Saharan African region. The methodology incorporates discursive analysis of existing technologies that will enable the country to make the right level of progress towards facilitating growth and development. The result unearthed gaps in provision, which is not so much about casting blame, but the need to ensure resources are pulled to address the scope for economic progression across all sectors, while at the same time adding value to the human resource skillset. The conclusion shows that resources should be pulled to make sure the system is ready to leap in a bid to embracing advances in technology modernisation needed to achieve sustained level of growth in the economy.